Mira – contemporary visual arts of indigenous peoples: introduction (2014)
The project Mira! Contemporary Visual Arts of the Indigenous Peoples was born with the aim of bringing together the many world views of the native peoples of the immense pan-Amazonian region. The project Mira!, with the exhibition of 125 works of indigenous artists (paintings, sculptures, digital art), seeks to show to the public that, alongside the aesthetics of the Western world, there are other ones that have arisen from other environments. Fifty four indigenous artists from Brazil, Bolivia, Colombia, Ecuador and Peru are participating in the Mira! Exhibition. Some of these artists were invited to expose their thoughts and to debate about their visions in a seminar that took place in Belo Horizonte in June 2013, when Mira! was inaugurated.